(untitled) (Revista Contexto & Saúde, 2022)
Pregnancy can be defined as a period of approximately 40 weeks, in which physiological and mechanic adaptations occur, along with strong psychological modifications. Being a moment of vulnerability, it can be negatively influenced by factors such as urinary incontinence (UI), high-risk pregnancy or even a negative body image. Thus, the aim of this study was to compare body image and the occurrence of urinary incontinence in high-risk and usual risk pregnant women. An observational study with a quantitative and cross-sectional approach was conducted to evaluate the occurrence of urinary incontinence and body image of pregnant women. The sample was divided into two groups: high-risk (n=34) and usual risk (n=31) pregnant women. For the data collection, an identification file was applied, collecting data such as obstetric history, followed by the International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF), and the Body Image Measurement Scale (BIMS). It was observed that both groups were dissatisfied with body image, and urinary incontinence occurrence was moderately above to what is found in literature. No relationship between urinary incontinence and body satisfaction was observed in either group. There was no relationship between urinary incontinence and body image. The pregnant women from both groups presented dissatisfaction regarding body image, and the occurrence of urinary incontinence was slightly higher than that observed in literature (50% of occurrence according to national estimates, especially during pregnancy and puerperium).